Advanced materials to enhance the nuclear performances of the high temperature Dual Coolant Lithium lead breeding blanket for the EU DEMO - David Sosa; Iole Palermo; Iván Fernández-Berceruelo; Javier Alguacil; Juan Pablo Catalán; María González; Julián Patiño (Nuclear Materials and Energy, 2025)
The evolution of the Dual Coolant Lithium Lead (DCLL) Breeding Blanket (BB) in the EUROfusion framework has led to the implementation of a Single Module Segment (SMS) architecture whose particularity is that it introduces the use of ceramic channels through which the self-cooled breeder (PbLi) circulates, allowing for a High Temperature (HT) concept. Among other candidates, SiC was initially selected. This HT SMS concept has shown certain drawbacks from the neutronic point of view. In particular, it was observed that this concept led to a decrease of the Tritium Breeding Ratio (TBR) below the required value (1.15 for DEMO). In this study we propose the addition of a specific component behind the breeding zone that acts either as a neutron reflector or as a better shield against radiation, in order to recover the TBR in a direct or indirect manner. The use of ZrH2 is preferred for this purpose as it allows combining both effects. On the other hand, there was a certain risk that SiC could not withstand the mechanical loads, so other ceramics (ZrO2, SiO2 and MgAl2O4) have been considered and their neutronic behaviour has been analysed. The use of ZrO2 has shown the best results in comparison with the other proposed, as a TBR of 1.17 (or 1.15 with a revised DCLL model) was achieved and improved all the shielding responses. Lastly, two different ZrO2 compositions that include industrial impurities and additives have been analysed to characterize their radiological behaviour and classify the radioactive waste following the international regulations.